ANALISIS PELAPORAN SPT TAHUNAN BADAN PADA CV JS MELALUI E-FORM 1771 - Triwanti Rosada, Cherli; Sucahyati, Diarany (Universitas Logistik dan Bisnis Internasional, 2025)
In an effort to enhance taxpayer compliance, the Directorate General of Taxes (DJP) has implemented a new innovation in the tax administration system, namely e-form. This study aims to thoroughly examine the effectiveness of CV JS Corporate Tax Return (SPT) reporting through e-form 1771. A qualitative descriptive approach is adopted to collect and analyze primary and secondary data related to the CV JS Corporate Tax Return (SPT) filling process. Primary data is obtained through direct interviews with CV JS tax consultants and direct observation of the annual corporate tax return filling process. Secondary data is obtained from scientific literature related to Corporate Tax Return (SPT) and e-form 1771. The objective of this study is to gather empirical evidence on the implementation of e-form in CV JS Corporate Tax Return (SPT) reporting that provides convenience for taxpayers. It is expected that the implementation of e-form can be a cutting-edge innovation and a reference for other companies in implementing e-form SPT Annual Body 1771 in their tax reporting, so that state tax revenue can be optimized on an ongoing basis. Keywords: Tax, Annual SPT, E-form 1771 Dalam rangka meningkatkan kepatuhan wajib pajak, Direktorat Jenderal Pajak (DJP) mengimplementasikan inovasi baru dalam sistem administrasi perpajakan, yaitu e-form. Penelitian ini bertujuan untuk mengkaji secara mendalam efektivitas pelaporan SPT Badan CV JS melalui e-form 1771. Pendekatan kualitatif deskriptif diadopsi untuk mengumpulkan dan menganalisis data primer dan sekunder terkait proses pengisian SPT Badan CV JS. Data primer diperoleh melalui wawancara langsung dengan konsultan pajak CV JS dan observasi langsung terhadap proses pengisian SPT tahunan badan. Adapun data sekunder diperoleh dari literatur ilmiah terkait SPT Tahunan Badan dan e-form 1771. Tujuan penelitian ini adalah untuk mengumpulkan bukti empiris mengenai penerapan e-form dalam pelaporan SPT Tahunan Badan CV JS yang memberikan kemudahan bagi wajib pajak. Diharapkan penerapan e-form ini dapat menjadi inovasi mutakhir dan acuan bagi perusahaan lain dalam menerapkan e-form SPT Tahunan Badan 1771 dalam pelaporan pajaknya, sehingga dapat mengoptimalkan penerimaan pajak negara secara berkelanjutan.